Precious pills : medicine and social change among Tibetan refugees in India - Prost, Audrey, 1977- (Epistemologies of healing, 2008)
When people are displaced, their social systems move with them. This book investigates what happens to traditional medical systems when they are "uprooted", i.e. when practitioners and patients become displaced, by looking at the transformations of traditional Tibetan medicine among the Tibetan refugee community in India. It addresses how long-term displacement affects concepts of health and examines the success and efficacy of Tibetan medicine in the context of social upheaval.